Silicosis in barium miners. Issue 8 (August 1986) - Seaton, A; Ruckley, V A; Addison, J; Brown, W R
Abstract : Four men who mined barytes in Scotland and who developed pneumoconiosis are described. Three developed progressive massive fibrosis, from which two died; and one developed a nodular simple pneumoconiosis after leaving the industry. The radiological and pathological features of the men's lungs were those of silicosis and high proportions of quartz were found in two of them post mortem. The quartz was inhaled from rocks associated with the barytes in the mines. The features of silicosis in barium miners are contrasted with the benign pneumoconiosis, baritosis, that occurs in workers exposed to crushed and ground insoluble barium salts. Diagnostic difficulties arise when silicosis develops in workers mining minerals known to cause a separate and benign pneumoconiosis. These difficulties are compounded when, as not infrequently happens, the silicotic lesions develop or progress after exposure to quartz has ceased.